Tourism and the Sharing Economy : Policy and Potential of Sustainable Peer-to-Peer Accommodation - Bakker, Martine; Twining-Ward, Louise (World Bank, Washington, DC, 2018)
Technology and digital platforms are disrupting the way the tourism sector operates from end to end affects low-income markets striving to leverage tourism for development impacts. Digital platforms, in particular, provide both opportunities and challenges for World Bank Group client countries looking to harness tourism to help achieve the World Bank Group's twin goals of ending extreme poverty and boosting shared prosperity. This report focuses on one disruptive force in the tourism industry: the emergence of peer-to-peer (P2P) accommodation. P2P accommodation occurs when individuals offer, in exchange for money, a room or an entire house for short-term accommodation. The rapid growth of this new product is shaking up the hotel industry and creating a new way to travel and interact with a destination and its community. The objectives of this report are to investigate the opportunities and challenges that P2P provides in developed and emerging destinations and to offer a set of recommendations to better use this new business model for sustainable and inclusive tourism. The report also sketches a research agenda for the near future. This report is written for destination managers, policymakers, and World Bank Group staff involved in the design and management of tourism operations.